(untitled) (Sustainability in Debate, 2016)
This article examines the legitimation of the paradigm of coexistence with the semiarid climate. It is based on the study a Municipal Plan for Coexistence with the Semiarid, drafted in 2014 for the municipality of Serra Talhada (in the interior of the state of Pernambuco). The methodology focused on the observation of meetings and events, on document analysis and on interviews with managers and stakeholders who dealt with the theme of coexistence in their fields. Results showed that the discourse of the coexistence emphasizes a leading role for civil society, but in practice it was found that there is a perverse confluence with the state. This transforms principles of social transformation into the reinstatement of old practices used to fight droughts. The configuration of the municipal plan under examination seems to work as a discursive tool intended to legitimize state actions that follow a paradigm that amounts to a political project for the modernization of the semiarid region.